Relação de cuidado com o outro na enfermagem: um estudo sobre o processo formativo de enfermeiros(as) - Fonseca, Sheila Cristina Teixeira (Universidade do Vale do Rio dos Sinos, 2019)
This dissertation sought to tackle the following research problem: how does the notion of care with others is approached in nurses’ educational process? As specific objectives, the study intended: to study the notion of caring for each other in the interface; to analyze educational assumptions related to the education of nurses in the Course Political Project (PPC) of the researched institution; to identify technical notions of care with others in specific subjects of the analyzed course; and to understand the way professors of this institution have approached or not the notion of care in the nurses' educational process. In this regard, it used as methodological procedures: documentary analysis and semi-structured interviews with professors that teach in the referred Nursing undergraduate course. The study was organized in six chapters that approached: the historical and legal aspects of Nursing; the ethical and legal conquest of Nursing as a profession, transforming care not only into a humanitarian practice, but into a science; the relation between education and care in Nursing; and the presentation of the analyses conducted in this research. The analytical chapter was organized in three sections: analysis of the Pedagogical Project of the Nursing Course (PPC) and of the summaries of the Course's subjects; description of the professors’ profiles of the analyzed Nursing Course; and analysis of the way the professors have approached or not the notion of care in nurses' educational process. Among the main findings of this research, it is possible to highlight: the understanding of the historicity of the Nursing undergraduate courses in Brazil; the process of professionalization of nurses; the understanding of the meanings of “caring” in a challenging professional daily routine, with low investments and little professional valuation; the importance of the educational process of nurses so that they "take better care” of their patients; and a broader knowledge about the analyzed Nursing undergraduate course, including the profile of the professors and the way the notion of care appears in the developed practices, so that this study will serve as basis for the possible further curricular developments in the researched institution.
Keywords: Educação; Enfermagem; Cuidado; Formação de enfermeiros(as); Education; Nursing; Care; Nurses' education; ACCNPQ::Ciências Humanas::Educação